2017
DOI: 10.1038/srep45744
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-dependent fluorescence recovery of NADH after photobleaching to assess dehydrogenase activity of isolated perfused hearts

Abstract: Reduction of NAD+ by dehydrogenase enzymes to form NADH is a key component of cellular metabolism. In cellular preparations and isolated mitochondria suspensions, enzyme-dependent fluorescence recovery after photobleaching (ED-FRAP) of NADH has been shown to be an effective approach for measuring the rate of NADH production to assess dehydrogenase enzyme activity. Our objective was to demonstrate how dehydrogenase activity could be assessed within the myocardium of perfused hearts using NADH ED-FRAP. This was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
(90 reference statements)
0
5
0
Order By: Relevance
“…For NADH-dependent enzymes, an enzyme-dependent fluorescence recovery after photobleaching (ED-FRAP) assay can also be used [124]. It relies on the photobleaching of a fluorophore as a product of an enzymatic reaction; in this case, NADH.…”
Section: Fragment-hit Qualificationmentioning
confidence: 99%
“…For NADH-dependent enzymes, an enzyme-dependent fluorescence recovery after photobleaching (ED-FRAP) assay can also be used [124]. It relies on the photobleaching of a fluorophore as a product of an enzymatic reaction; in this case, NADH.…”
Section: Fragment-hit Qualificationmentioning
confidence: 99%
“…Changes in NADH autofluorescence are also reflecting the response of the respiratory chain to exposure to metabolic substrates or poisons, or to changes in oxygen availability, with implications also for the set-up of strategies in the monitoring of organ functionality during the transplantation phases [47,295,[306][307][308][309][310]]. An improvement in fluorescence studies of cytoplasmic metabolic functions is also promised by technological advances in imaging microscopy based on fluorescence lifetime detection, allowing to exploit the differences in lifetime between NADH and NADPH in living cells to study separately the metabolic engagement of the two derivatives, mainly as to energy production and antioxidant defense [173,291].…”
Section: Normal and Altered Cell And Tissuesmentioning
confidence: 99%
“…Reperfusion injury is often characterized with a return of blood supply resulting in cellular cardiac death, and is often characterized with infarct zones. Reperfusion injury has been associated with a significant increase in NADH levels (Moreno et al, 2017). We demonstrated that the pre-and post-exposure to P7C3 in an ex vivo Langendorff system provided significant protection in db/db hearts.…”
Section: P7c3 Enhanced Nampt Activity In Vitro Andmentioning
confidence: 75%